2013
DOI: 10.1351/pac-con-12-08-13
|View full text |Cite
|
Sign up to set email alerts
|

Stereocontrolled 1-S-glycosylation and comparative binding studies of photoprobe-thiosaccharide conjugates with their O-linked analogs

Abstract: The use of thioglycosides and other glycan derivatives with anomeric sulfur linkages is gaining increasing interest, both in synthesis and in various biological contexts. Herein, we demonstrate the occurrence and circumvention of anomerization during 1-S-glycosylation reactions, and present highly efficient and stereocontrolled syntheses of a series of photoprobe-thiosaccharide conjugates. Mutarotation of glycosyl thiols proved to be the origin of the anomeric mixtures formed, and kinetic effects could be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…Of note, these results agree with those of a recently reported comparative binding study of S-and O-glycoconjugates to different lectins, which showed that both types of derivatives exhibited similar affinities. 33 To explain these experimental results, a putative 3D model of the complex of 10f with SBA was established using MD simulations ( Figure 7a). As expected, these calculations indicate that compound 10f interacts with the lectin mainly through the carbohydrate moiety.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Of note, these results agree with those of a recently reported comparative binding study of S-and O-glycoconjugates to different lectins, which showed that both types of derivatives exhibited similar affinities. 33 To explain these experimental results, a putative 3D model of the complex of 10f with SBA was established using MD simulations ( Figure 7a). As expected, these calculations indicate that compound 10f interacts with the lectin mainly through the carbohydrate moiety.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Accordingly, there are a few reports of mutarotation during 1-S-glycosylation and similar reactions. 39,41,42 Anomerization of glycosyl thiols was also noticed in reactions with Lewis acids such as TiCl 4 and SnCl 4 . In uronic acids such anomerization is particularly fast, presumably favoured by coordination of the C-1 heteroatom and C-6 carbonyl group to the Lewis acid.…”
Section: Discussionmentioning
confidence: 89%
“…The configurational stability of glycosyl thiols could be partially explained by poor orbital overlap between the anomeric carbon and the sulphur atom, which does not favor opening and subsequent mutarotation of the pyranose ring. 39 However, it was shown that in aqueous media mutarotation of free glycosyl thiols occurs at lower and neutral pH, while it is almost completely blocked under basic conditions. An exception is 1-thio-D-mannopyranose that was observed to mutarotate under both acidic and basic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, real‐time monitoring of the binding events and additional binding kinetics data can be obtained with biosensors like SPR and quartz crystal microbalance (QCM) . Isothermal titration calorimetry (ITC) can provide thermodynamic information, and detailed single molecular interaction data can be acquired by using AFM . Combination of microarrays with nanotechnology can greatly enhance the sensitivity of detection .…”
Section: Discussionmentioning
confidence: 99%